TREOSULFAN-BASED CONDITIONING REGIMEN IN SIBLING AND ALTERNATIVE DONOR HEMATOPOIETIC STEM CELL TRANSPLANTATION FOR CHILDREN WITH SICKLE CELL DISEASE - Antonio Marzollo; Elisabetta Calore; Manuela Tumino; Marta Pillon; Maria Vittoria Gazzola; Roberta Destro; Raffaella Colombatti; Piero Marson; Tiziana Tison; Anna Colpo; Chiara Mainardi; Maria Gabelli; et al. (Mediterranean Journal of Hematology and Infectious Diseases, 2017)
Background and objectives  Lack of suitable donors and regimen related toxicity are major barriers for hematopoietic stem cell transplantation (HSCT) in patients with sickle cell disease (SCD) when employing the most frequently used Busulfan-based conditioning regimen. The aim of the study is the assessment of efficacy and toxicity of Treosulfan-based conditioning regimen for SCD also when alternative donors such as mismatched unrelated donor and haploidentical donor are employed. Methods We report our single-center experience: 11 patients with sickle cell disease received HSCT with a Treosulfan/Thiotepa/Fludarabine/Anti-thymoglobulin conditioning regimen between 2010 and 2015. The donor was a matched sibling donor (n= 7), a haploidentical parent (n= 2), a matched unrelated donor (n= 1) or a mismatched unrelated donor (n=1). The haploidentical and mismatched unrelated donor grafts were manipulated by removing TCRαβ and CD19 positive cells. Results All patients survived the procedure and achieved stable engraftment. Stable mixed chimerism but no SCD manifestation was observed in 5/11 patients. Grade III-IV regimen related toxicity was limited to mucositis and no grade III-IV graft-versus-host disease (GvHD) was observed. Organ function evaluation showed no long term pulmonary, cardiac or renal toxicity; cerebral vasculopathy improved in 3/5 evaluable patients. Gonadal failure was observed in 1/4 evaluable patients. Conclusion Our data suggest that Treosulfan retains the myeloablative potential of Busulfan while reducing the toxicity also when haploidentical or unrelated donors are employed.